Justice: the Conformance to Reality - Sayyid Abd al-RaÙf Afzali (حکمت اسرا, 2011)
The issue of justice is an important topic particularly from a political-philosophical dimension. By relying on the theoretical principles underlying AyatullahJawÁdÐÀmulÐ’s views and by analyzing his thoughts from his various works, the author has attempted to seek out Ayatullah JawÁdi’s understanding of this concept. According to Ayatullah JawÁdi, justice is no different from conforming to reality. Apart from the fact that this understanding is in harmony with the respected scholar’s philosophical approach—which is the approach of Transcendental Theosophy—it is corroborated through numerous instances and examples found within his works. This understanding also carries its own necessary implications and particular consequences which, in the realm of the philosophy of politics, leads it to presenting and confirming the government of the infallible. The governance of the jurist is logical extension of this.